Acute respiratory insufficiency after endoscopy for bleeding oesophageal varices. Issue 6431 (2nd June 1984) - Crawford, D C; Ryan, D W
Abstract : Two patients with alcoholic liver disease and gross ascites underwent endoscopic injection and compression by Sengstaken tube of oesophageal varices under general anaesthesia. Postoperatively both patients developed acute respiratory failure, which resolved after air had been aspirated from the stomach via the Sengstaken tube. All air should be aspirated at the end of the procedure in patients with ascites who undergo endoscopy, and respiration should be carefully supervised postoperatively.